Ibn Duraid's Linguistic Thought and Its Influence in Arabic Dictionary - Sulistya Sulistya; Jarot Wahyudi; Huseyin Emin Sert (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. This study focuses on critically analyzing the method and influence of the dictionary "al-Jamharah," composed by the prolific scholar Ibn Duraid. The development of Arabic vocabularies is essential for understanding the language, and dictionaries play a crucial role as the primary reference for word meanings. Purpose. The main aim of this research is to explore and critically analyze the methods employed by Ibn Duraid in compiling the "al-Jamharah" dictionary. The study seeks to understand how this dictionary contributed to the development of Arabic lexicography and the influence it had on subsequent linguistic studies. Method. The research employs a literature review method, which includes collecting bibliographic data, reading, taking notes, and analyzing various sources related to the "al-Jamharah" dictionary. This method allows for a comprehensive examination of the historical context, methodologies, and impact of Ibn Duraid’s work on Arabic lexicography. Results. The study finds that the "al-Jamharah" dictionary by Ibn Duraid is notable for being the first to use an alphabetical order system, specifically the "aba-jad-un" order. This system was developed to address the difficulties faced by Arabs in understanding the phonetic ordering formed by al-Khalil. The alphabetical method significantly simplified the process of searching for word meanings compared to the traditional phonetic system. Conclusion. The research concludes that the alphabetical system introduced in "al-Jamharah" provided significant advancements in the field of lexicology, distinguishing it from other linguistic sciences such as qira’at, tajwid, and tafsir.